Theoretical and Methodological Issues of Modernization of Technology Education - Boybalayev Mirzookhun Abdumanonovich (Zien Journals, 2022)
In this article, topics such as modernization of technology science based on the requirements of the labor market, sustainable development from a socio-economic point of view, application of the knowledge, skills and qualifications acquired by students in the course of technical-technological and technological process operations in their independent practical activities are discussed. will be considered
Keywords: increasing competitiveness; obsolescence of infrastructure; labor migration; introduction of advanced technologies